Covered stent placement for treatment of coarctation of the aorta: immediate and long-term results. Issue 5 (16th July 2021) - Stassen, Jan; De Meester, Pieter; Troost, Els; Roggen, Leen; Moons, Philip; Gewillig, Marc; Van De Bruaene, Alexander; Budts, Werner
Abstract: Objectives: This study aimed to describe the safety and efficacy of covered stents in patients with coarctation of aorta (CoA) for immediate and long-term follow-up. Background: Covered stents are increasingly being used in (re)CoA, mainly to reduce the risk of aortic wall injuries (AWI). However, limited data are available on intermediate and long-term outcome. Methods: In 89 patients (67.4% male) with a mean age of 23.9 ± 15.8 (min max range 5.1–71.6) years were 102 covered stents implanted (January 2003 – December 2017). Short-term pre/post-implant hemodynamics and angiographic data were reported. Changes in blood pressure, the use of antihypertensive drugs and complications were recorded during follow-up. Results: The procedural success rate was 100%. The mean invasive ascending-to-descending aorta systolic gradient under general anaesthesia decreased from 25 ± 16 mmHg to 4 ± 7 mmHg ( p < 0.001). After a mean follow-up time of 6.6 ± 3.7 years, there was a persistent improvement of the mean systolic blood pressure gradient between right arm and leg (−7 ± 18 vs 38 ± 24 mmHg; p < 0.001). A larger proportion of patients required antihypertensive medication (33.7% vs 50.0%, p = 0.017) and needed ≥ 2 drugs (20.2% vs 27.4%, p = 0.066) to control blood pressure. Long-term adverse events were found in 4.5% of patients [covered stent fracture ( n = 3), aneurysm formation ( n = 2)]. Conclusions: Covered stent implantation for CoA is highly successful, safe and results in a persistent hemodynamic improvement in the immediate and long-term outcome. Lifelong follow-up with additional antihypertensive drug treatment is mandatory to maintain favourable hemodynamic results after stenting. CONDENSED ABSTRACT: Long-term follow-up data on covered stents in patients with coarctation of the aorta are scarce. A cohort of 89 patients was reviewed. The procedural implantation success rate was 100%. The invasive gradient decreased from 25 ± 16 mmHg to 4 ± 7 mmHg ( p < 0.001). After follow-up of 6.6 ± 3.7 years, there was a persistent improvement of the clinical systolic blood pressure gradient (−7 ± 18 vs 38 ± 24 mmHg; p < 0.001). However, a larger proportion of patients required antihypertensive medication (33.7% vs 50.0%, p = 0.017). Covered stent implantation results in favourable hemodynamic effects, but lifelong follow-up with additional antihypertensive drug treatment is mandatory to maintain these results.